Deleuze and desire: Analysis of the logic of sense - Swiatkowski, Piotrek (Leuven Leuven University Press, 2015)
The engagement of Gilles Deleuze with psychoanalysis has led to the development of a remarkable and highly influential theory about human desire. The most systematic account of this theory, crucial for anyone interested in the work of Deleuze and Félix Guattari, can be found in the discussion of the dynamic genesis of sense, a pivotal part of Deleuze's The Logic of Sense. In Deleuze and Desire Piotrek Zwitkowski picks up the challenge to provide a commentary on this text. Zwitkowski makes use of a broad range of examples, from psychoanalytic case studies to art, literature, and film, and systematically analyzes in an accessible and clear way the impact of the work of psychoanalysts such as Melanie Klein on Deleuze.